Oil Palm and Deforestation in Papua New Guinea - Nelson, P.; Gabriel, J.; Filer, C.; Banabas, M.; Sayer, J.; Curry, George; Koczberski, Gina; Venter, O. (Wiley-Blackwell, 2014)
An unprecedented increase in oil palm developments may be underway in Papua New Guinea (PNG) through controversial “special agricultural and business leases” (SABLs) covering over two million hectares. Oil palm development can create societal benefits, but doubt has been raised about whether the SABL developers intend establishing plantations. Here, we examine the development objectives of these proposals through an assessment of their land suitability, developer experience and capacity, and sociolegal constraints. Our review reveals 36 oil palm proposals with plantings planned for 948,000 ha, a sevenfold increase over the existing planted area in PNG. Based on our criteria, however, we estimate that only five plantations covering 181,700 ha might eventuate within the foreseeable future. We conclude that most of the developers are clearing forest with no intention of cultivating oil palm, and that a large-scale land grab is therefore occurring in PNG under the guise of oil palm development.